Antimicrobial Activity of Selenium Nanoparticles Synthesized by Actinomycetes Isolated from Lombok Island Soil Samples - Shanti Ratnakomala; Nurul Fitri Sari; Fahrurrozi Fahrurrozi; Puspita Lisdiyanti (Research Center for Chemistry - LIPI, 2018)
AbstractA total of 98 actinomycetes were isolated from the soil and litter samples collected from the cacao and coffee plantation in Lombok Island, West Nusa Tenggara, Indonesia. These isolates were screened for their antimicrobial activity. Among 98 isolated strains, only 24 isolates showed antimicrobial activity against test microorganisms of which 20.4% were active against Bacillus subtilis BTCC B-612, 14.3% against Staphylococcus aureus BTCC B-611, and 5.1% against Escherichia coli BTCC B-609. Out of these 24 isolates, 3 were found to be able to grow in medium containing 3 mM Selenium oxide of which the culture were changed color to red. Two of the best strains, L-155 and L-156, were selected for assessing production of Selenium nanoparticles. Bioreduction of selenium nanoparticles was confirmed by UV–visible spectrophotometer which showed peak between 300 and 320 nm. Biosynthesized selenium nanoparticle from isolate actinomycetes L-155 and L-156 were found to have a broad spectrum of activity against the tested microorganisms: Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Micrococcus luteus, and Candida albicans. This study showed rapid and eco-friendly synthesis of selenium nanoparticles from soil actinomycetes. Most of these active isolates revealed to possess antibacterial property.